PENGAWASAN PEREDARAN PRODUK PANGAN MINUMAN IMPOR DI KOTA PEKANBARU - Febi Febiola; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Distribution of imported beverage products that are not in accordance with the applicable provisions is still a problem for the people of Pekanbaru. It can be seen from the number of imported beverage distributors that do not get controlling from BBPOM and DISPERINDAG Pekanbaru, there are still many circulating imported beverage products that do not have distribution license, expiry and packaging of dent, there are still many business perpetrators who committed violation and lack of knowledge about the society Imported beverage products that meet the requirements in accordance with the prevailing provisions that are guaranteed to be safe and fit for consumption. This research was conducted to know the controlling conducted by BBPOM and DISPERINDAG on the circulation of imported beverage products in Pekanbaru. By looking at the controlling of BBPOM and DISPERINDAG Pekanbaru to the distribution of imported beverage products in Pekanbaru. The research was conducted using qualitative method with descriptive research type. This research uses Manullang's supervisory theory by setting standards, conducting assessment actions and performing corrective actions. In this research, the techniques are observation, interview and documentation using qualitative descriptive analysis technique. The results of this study indicate that controlling of the circulation of imported beverage products by BBPOM and DISPERINDAG in Pekanbaru is still not running well due to the lack of guidance to business actors and the community, unresolved legal sanctions, still minimal number of employees and number of operational vehicles, Public participation in controlling of the circulation of imported beverage products in Pekanbaru. Therefore, in an effort to optimize the controlling of the circulation of imported beverage products, it is necessary to improve the guidance to businesses and communities, to give strict legal sanctions, and to increase the number of employees and operational vehicles BBPON and DISPERINDAG Pekanbaru.Keywords: control, Distribution Facility, BBPOM and DISPERINDAG